Cohesion metric for java inner class - Tee, Sim Hui (2012)
Inner class is a helper class that is declared within the body of another class. To date,there is no cohesion metric specially designed for the inner classes. In current practice,the cohesion of inner classes is measured using the class cohesion metrics. However, the existing practice does not obtain the actual cohesion of inner class because the role of inner class as a helper class for its outer class is not evaluated. In this thesis, the cohesion of inner class is measured in term of the single functionality it has fostered for the outer class as a whole. A total of 74 inner classes from 15 applications were investigated. This research presents a novel twofold approach in measuring the in-bound cohesion and outbound cohesion for inner classes. The results demonstrate that the proposed metric, namely Inner Class Based-ELCOM (IELCOM), is an improvement of its predecessor External Lack of Cohesion Metric (ELCOM) in terms of measuring the cohesion of inner class. This proposed approach enables the software practitioners to recognize the cohesion of an inner class by considering the functional relationship between inner and outer class as an integrated whole.